At a restaurant Mike and his three friends that means that there was four people splitting the bill. If each of them paid $13 then the bill was $52
4 * 13 = $52
Answer:
f(18)=334
Step-by-step explanation:
- f(x)=13x+100
- f(18) = 13(18)+100
- f(18)=234+100
- f(18)=334
Answer:
red balls = 5
blue balls = 5
total balls = 5 blue+5 red
= 10
![p(first \: ball \: being \: red) = \frac{red \: balls}{total \: balls}](https://tex.z-dn.net/?f=p%28first%20%5C%3A%20ball%20%5C%3A%20being%20%5C%3A%20red%29%20%3D%20%20%5Cfrac%7Bred%20%5C%3A%20balls%7D%7Btotal%20%5C%3A%20balls%7D%20)
![p(first \: ball \: being \: red) = \frac{5}{10} = \frac{1}{2}](https://tex.z-dn.net/?f=p%28first%20%5C%3A%20ball%20%5C%3A%20being%20%5C%3A%20red%29%20%3D%20%20%5Cfrac%7B5%7D%7B10%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20)
There is no common factor between 15, 17 and 18 because 17 is prime.
15z² +17z - 18 =
d = 17² - 4.15.-18
d = 289 + 1080
d = 1369
z = (-17 +/- \/1369) : 2 * 15
z = (-17 + 37) : 30
z' = 20 : 30 = 2/3
z" = (-17 - 37) : 30
z" = -54 : 30 = -1.8
<><
![\frac{ {x}^{2} - 7x + 12}{ {x}^{2} - x - 12 } \\ = \frac{ {x}^{2} - 4x - 3x + 12 }{ {x}^{2} - 4x + 3x - 12 } \\ = \frac{x(x - 4) - 3(x - 4)}{x(x - 4) + 3(x - 4)} \\ = \frac{(x - 3)(x - 4)}{(x + 3)(x - 4)} \\ = \frac{x - 3}{x + 3}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%20-%207x%20%2B%2012%7D%7B%20%7Bx%7D%5E%7B2%7D%20-%20x%20-%2012%20%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20-%204x%20-%203x%20%2B%2012%20%7D%7B%20%7Bx%7D%5E%7B2%7D%20-%204x%20%2B%203x%20-%2012%20%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7Bx%28x%20-%204%29%20-%203%28x%20-%204%29%7D%7Bx%28x%20-%204%29%20%2B%203%28x%20-%204%29%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%28x%20-%203%29%28x%20-%204%29%7D%7B%28x%20%2B%203%29%28x%20-%204%29%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7Bx%20-%203%7D%7Bx%20%2B%203%7D%20)
x² - x - 12 ≠ 0
x² - 4x + 3x - 12 ≠ 0
x (x - 4) + 3 (x - 4) ≠ 0
(x + 3)(x - 4) ≠ 0
x ≠ -3 or x ≠ 4
(B)